Self-fashioning exceptionality: flexible workers in Singapore's casino resorts. Issue 1 (2nd January 2017) - Zhang, Juan; Yeoh, Brenda S.A.; Ramdas, Kamalini
Abstract : This article investigates the embodied experiences of "exceptionality" of casino resort employees in Singapore. Working in Singapore's newly-opened mega-casino resorts, migrant and local employees claim a sense of agency over their own professionalism, mobilities, and moralities. Actively equipping themselves with expertise, knowledge, experiences, and certain moral attitudes, casino employees practice a particular kind of "self-fashioning" suited for the global labor market. The "self-fashioning" is oriented towards becoming "exceptional, " in the sense that casino employees are encouraged to be highly skilled, well connected, globally mobile, and keenly self-disciplined. However, the more casino employees are conditioned by codes of "exceptionality, " the more vulnerable they are when faced with career insecurities, future uncertainties, and moral dilemmas. This article argues that the self-fashioning of casino employees can be both empowering and suppressing. While waged employees are eager to participate in the flexible labor market, they are also held captive by the regime of exceptionality.